The impact of the EU-US open skies agreement on international travel and carbon dioxide emissions - Karen Mayor; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2007)
We use a model of domestic and international tourist numbers and flows to estimate the impact of the EU-US Open Skies agreement that is to take effect in March 2008. The Open Aviation Area will result in increased competition between transatlantic carriers and consequently falls in the cost of flights, therefore we look at the change in visitor numbers from the US into the EU and corresponding CO2 emissions. We find that passenger numbers arriving from the US to the EU will increase by approximately 1% and 14% depending on the magnitude of the price reductions. This increase in passenger numbers does not however result in a corresponding rise in emissions as arrivals into other countries from the US fall by a comparable amount. The number of tourist arrivals from the US to countries outside of the EU will fall and overall emissions would then increase by a maximum of 0.7%. If we assume that domestic holidays and foreign holidays are close substitutes these effects are strengthened and US passengers switch from domestic trips to foreign destinations as airfares converge.
Keywords: 330; International tourism; open skies agreement; carbon dioxide emissions; Internationaler Tourismus; Luftverunreinigung; Kohlendioxid; Luftverkehrspolitik; USA; EU-Staaten